Analysis of Implementation Scout Extracurricular on Disciplinary Character Students MI Imam Puro Cangkrep Kidul - Auliya, Fatma Nur; Nurhidayati, Nurhidayati; anjarini, Titi (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to determine the extracurricular scouting program that can foster discipline and analyze how it is applied to the discipline of students at MI Imam Puro Cangkrep Kidul Purworejo. The type of research used is descriptive qualitative. The subjects of this study were students who took part in the scouting extracurricular, namely grade III and IV students at MI Imam Puro Cangkrep Kidul with a total of 15 students taken using the cluster sampling technique. Data collection techniques in this study used observation, questionnaires, interviews, and documentation. The data analysis techniques used were data reduction, data display, and drawing conclusions. This study obtained results that there are several extracurricular scouting programs that can foster students' discipline, namely routine training, scout opening and closing ceremonies, Friday and Saturday camps (Perjusa), and PBB. The supporting factors for students' discipline are the role of parents, the role of teachers at school, and self-awareness. As well as the inhibiting factors for students' discipline are self-awareness and peer factors. This study also obtained results that the character of student discipline through the MI Imam Puro Cangkrep Kidul scout extracurricular is in a good classification as seen from three indicators, namely: 1) discipline towards time, 2) discipline towards rules, and 3) discipline in dressing. This study is expected to increase knowledge and insight for the development of science, especially in the application of scouting education to student character.